The Impact Of Respiratory Therapy Interventions On Patient Outcomes Across Acute, Chronic, And Critical Care Settings: A Comprehensive Review (The Review of Diabetic Studies, 2024)
This comprehensive review examines the impact of respiratory therapy (RT) interventions on patient outcomes across acute, chronic, and critical care settings. Respiratory therapists play a pivotal role in the management of respiratory failure, chronic pulmonary diseases, and life-threatening emergencies through evidence-based interventions including oxygen therapy, mechanical ventilation, airway clearance techniques, pulmonary rehabilitation, and patient education. This review synthesizes contemporary evidence on the clinical effectiveness of RT interventions in improving physiological outcomes, reducing morbidity and mortality, enhancing patient safety, and optimizing healthcare system performance. A structured review methodology was employed to analyze studies published in recent years, focusing on outcome measures such as survival rates, hospital length of stay, readmission rates, functional capacity, and quality of life. Findings demonstrate that integrated respiratory therapy services significantly contribute to improved patient outcomes across the care continuum, particularly when embedded within multidisciplinary care models and supported by digital health technologies. The review highlights the evolving scope of respiratory therapy practice and underscores its strategic importance in modern healthcare systems. Implications for clinical practice, workforce development, and health policy are discussed.